Acute Effect of Kinesiology Taping on Postural Stability in Individuals With Unilateral Chronic Ankle Instability - Yin, Lulu; Wang, Lin (Frontiers in Physiology, 2020)
Background Chronic ankle instability (CAI), which is characterized by deficient postural control, could be improved through kinesiology taping (KT). However, the effect of KT on postural control in CAI individuals is controversial. Therefore, this study aimed to investigate the acute effect of KT on postural control through computerized dynamic posturography (CDP) and self-perceived sensation in CAI individuals. Methods Participants with CAI received four different ankle treatments randomly, including KT, athletic taping (AT), sham taping (ST), and no taping (NT). A series of postural stability measurements was performed using CDP subsequently. The measurements included sensory organization test (SOT), unilateral stance (US), limit of stability (LOS), motor control test (MCT), and adaption test (ADT). In addition, self-perceived sensation was measured through visual analog scaling. Repeated measures analysis of variance was conducted to determine whether the difference among KT, AT, ST, and NT was significant; Bonferroni test was used for post hoc analysis. Results No significant difference was observed for parameters in SOT, US, and LOS in four different taping treatments. In MCT, the amplitude scaling scores of KT were 35.87% significantly lower than that of NT [p < 0.001, 95% confidence interval (CI) = 0.548–1.795] in forward-small slip and 21.58% significantly lower than that of ST (p = 0.035, 95% CI = 0.089–3.683) in backward-large slip. In ADT, sway energy scores were 7.59% significantly greater in ST than in AT (p = 0.028, 95% CI = −8.343 to −0.320). For perceived stability, KT was significantly greater than ST (p < 0.001, 95% CI = 0.552–1.899) and NT (p < 0.001, 95% CI = 0.797–2.534), and AT was significantly greater than ST (p = 0.001, 95% CI = 0.423–2.246) and NT (p < 0.001, 95% CI = 0.696–2.852). For perceived comfort, KT was significantly greater than AT (p = 0.001, 95% CI = 0.666–3.196) and NT (p = 0.031, 95% CI = 0.074–2.332), and ST was significantly greater than AT (p = 0.007, 95% CI = 0.349–2.931). Conclusion KT and AT have limited effect to facilitate postural control for CAI individuals during SOT, US, and LOS. However, KT and AT could provide effective support to cope with sudden perturbation in MCT and ADT. Moreover, KT provided excellent perceived stability and comfort, whereas AT provided excellent perceived stability but least comfort.